Implementasi project based learning untuk meningkatkan aktivitas belajar siswa - Linda Kahar; La Ili (Universitas Indraprasta PGRI, 2022)
learning activities are a series of activities carried out by students to learn. Unfortunately, students' learning activities often decline due to many factors. Project based learning is considered capable of increasing student learning activities. This study aims to describe project based learning as a learning model to improve student learning activities. This study is the result of a literature review. The study in this study was analyzed based on supporting references that were considered valid. The limitations examined in this study are the definition, objectives, and steps of the project based learning model. The results of the study revealed that the project based learning model was able to increase student learning activities. It is hoped that teachers will be able to use this learning model to improve student learning activities.